Investigation of cell adhesion in chitosan membranes for peripheral nerve regeneration - Carvalho, C. R. (2017)
Peripheral nerve injuries have produced major concerns in regenerative medicine for several years, as the recovery of normal nerve function continues to be a significant clinical challenge. Chitosan (CHT), because of its good biocompatibility, biodegradability and physicochemical properties, has been widely used as a biomaterial in tissue engineering scaffolding. In this study, CHT membranes were produced with three different Degrees of Acetylation (DA), envisioning its application in peripheral nerve regeneration. The three CHT membranes (DA I: 1%, DA II: 2%, DA III: 5%) were extensively characterized and were found to have a smooth and flat surface, with DA III membrane having slightly higher roughness and surface energy. All the membranes presented suitable mechanical properties and did not show any signs of calcification after SBF test. Biodegradability was similar for all samples, and adequate to physically support neurite outgrowth. The in vitro cell culture results indicate selective cell adhesion. The CHT membranes favoured Schwann cells invasion and proliferation, with a display of appropriate cytoskeletal morphology. At the same time they presented low fibroblast infiltration. This fact may be greatly beneficial for the prevention of fibrotic tissue formation, a common phenomenon impairing peripheral nerve regeneration. The great deal of results obtained during this work permitted to select the formulation with the greatest potential for further biological tests.